Checklist of the Pipunculidae (Diptera) of mainland France: further faunistic records and description of a new species - Withers, Phil; Claude, Jocelyn (Zootaxa, 2021)
Since the first faunistic study of the Pipunculidae (Diptera) of mainland France in 2006, new material from 37 natural sites and four private collections has been evaluated by the authors of this article. A total of 5739 specimens of Pipunculidae collected in France were examined, of which 5214 were identified to species by the authors, for a total of 114 species. DNA analyses were also carried out on some specimens to confirm their morphological identifications. The list of Pipunculidae recorded in mainland France is updated to include 140 species. Tomosvaryella estebani sp. nov. is described from material collected in France and Italy. Twenty-four species are also reported for the first time from France. The records of Cephalops (Semicephalops) carinatus (Verrall, 1901), Cephalosphaera (Cephalosphaera) furcata (Egger, 1860), Eudorylas terminalis (Thomson, 1870) and Jassidophaga villosa (Roser, 1840), without precise data in the literature, are now precisely located in France with this work. For the other species, we provide new post-2006 records.